WinAlgos: software for algologists - Guido Orlandini; Mauro Montagni (Pathos)
WinAlgos is a software that was first developed in 2001 as a "computerised algological record" and later evolved into 2022 version as a tool to assist the algologist in examining patients and formulating accurate pathogenetic and syndromic diagnosis of pain.